THE FUNCTIONAL FEATURES OF INTERIOR DESIGN TERMINOLOGY IN ENGLISH AND UZBEK LANGUAGES - Xolmurotova Gulnora Sattorovna (Western European Studies, 2025)
This article examines the functional characteristics of interior design terminology in English and Uzbek. It explores the origins, linguistic and semantic features, as well as the challenges associated with translating and adapting these terms. The study identifies four main approaches to term formation in Uzbek: direct adoption, word-for-word translation, descriptive adaptation, and borrowing through Russian. The research highlights the importance of standardization in ensuring the effective use of terminology in professional communication and knowledge dissemination. The findings contribute to a better understanding of how interior design terms evolve across languages and provide insights into improving their translation and adaptation within the Uzbek linguistic and cultural context.
Keywords: interior design terminology; linguistic adaptation; translation challenges